Sodium Alginate-Based MgO Nanoparticles Coupled Antibiotics as Safe and Effective Antimicrobial Candidates against Staphylococcus aureus of Houbara Bustard Birds - Maheen Murtaza; Amjad Islam Aqib; Shanza Rauf Khan; Afshan Muneer; Muhammad Muddassir Ali; Ahmad Waseem; Tean Zaheer; Lamya Ahmed Al-Keridis; Nawaf Alshammari; Mohd Saeed (Biomedicines, 2023)
Alternative and modified therapeutic approaches are key elements in culminating antibiotic resistance. To this end, an experimental trial was conducted to determine the cytotoxicity and antibacterial potential of composites of magnesium oxide (MgO) nanoparticles and antibiotics stabilized in sodium alginate gel against multi-drug-resistant Staphylococcus aureus isolated from a houbara bustard. The characterization of preparations was carried out using X-ray diffraction (XRD), scanning transmissible electron microscopy (STEM), and Fourier-transform infrared spectroscopy (FTIR). The preparations used in this trial consisted of gel-stabilized MgO nanoparticles (MG), gel-stabilized tylosin (GT), gel-stabilized ampicillin (GA), gel-stabilized cefoxitin (GC), gel-stabilized MgO and tylosin (GMT), gel-stabilized MgO and cefoxitin (GMC), and gel-stabilized MgO and ampicillin (GMA). The study presents composites that cause a lesser extent of damage to DNA while significantly enhancing mitotic indices/phases compared to the other single component preparations with respect to the positive control (methyl methanesulphonate). It was also noted that there was a non-significant difference (p > 0.05) between the concentrations of composites and the negative control in the toxicity trial. Studying in parallel trials showed an increased prevalence, potential risk factors, and antibiotic resistance in S. aureus. The composites in a well diffusion trial showed the highest percentage increase in the zone of inhibition in the case of GT (58.42%), followed by GMT (46.15%), GC (40.65%), GMC (40%), GMA (28.72%), and GA (21.75%) compared to the antibiotics alone. A broth microdilution assay showed the lowest minimum inhibitory concentration (MIC) in the case of GMA (9.766 ± 00 µg/mL), followed by that of GT (13.02 ± 5.64 µg/mL), GMC (19.53 ± 0.00 µg/mL), GA (26.04 ± 11.28 µg/mL), GMT (26.04 ± 11.28 µg/mL), MG (39.06 ± 0.00 µg/mL), and GC (39.06 ± 0.00 µg/mL). The study thus concludes the effective tackling of multiple-drug-resistant S. aureus with sodium-alginate-stabilized MgO nanoparticles and antibiotics, whereas toxicity proved to be negligible for these composites.